PPAR-alpha dependent regulation of vanin-1 mediates hepatic lipid metabolism - van Diepen, Janna A.; Jansen, Patrick A.; Ballak, Dov B.; Hijmans, Anneke; Hooiveld, Guido J.; Rommelaere, Samuel; Galland, Franck; Naquet, Philippe; Rutjes, Floris P.J.T.; Mensink, Ronald P.; Schrauwen, Patrick; Tack, Cees J.; et al. (Journal of hepatology, 2014)
Peroxisome proliferator-activated receptor alpha (PPARα) is a key regulator of hepatic fat oxidation that serves as an energy source during starvation. Vanin-1 has been described as a putative PPARα target gene in liver, but its function in hepatic lipid metabolism is unknown. We investigated the regulation of vanin-1, and total vanin activity, by PPARα in mice and humans. Furthermore, the function of vanin-1 in the development of hepatic steatosis in response to starvation was examined in Vnn1 deficient mice, and in rats treated with an inhibitor of vanin activity. Liver microarray analyses reveals that Vnn1 is the most prominently regulated gene after modulation of PPARα activity. In addition, activation of mouse PPARα regulates hepatic- and plasma vanin activity. In humans, consistent with regulation by PPARα, plasma vanin activity increases in all subjects after prolonged fasting, as well as after treatment with the PPARα agonist fenofibrate. In mice, absence of vanin-1 exacerbates the fasting-induced increase in hepatic triglyceride levels. Similarly, inhibition of vanin activity in rats induces accumulation of hepatic triglycerides upon fasting. Microarray analysis reveal that the absence of vanin-1 associates with gene sets involved in liver steatosis, and reduces pathways involved in oxidative stress and inflammation. We show that hepatic vanin-1 is under extremely sensitive regulation by PPARα and that plasma vanin activity could serve as a readout of changes in PPARα activity in human subjects. In addition, our data propose a role for vanin-1 in regulation of hepatic TG levels during fasting.